"Goddam paper" – Translating Swearwords from English into Finnish : The Catcher in the Rye by J.D. Salinger as a Case in Point - Lahdenperä, Miljaana (My University, 2022)
This MA thesis studies the translation of swearwords from English into Finnish in the context of retranslation, with The Catcher in the Rye by J.D. Salinger as the case in point. The research is conducted by analysing the similarities and differences in the first Finnish translation by Pentti Saarikoski and the retranslation by Arto Schroderus. The research material collected for this thesis are the 50 first instances of the swearwords damn or goddam in the original English novel. The swearwords are collected from the original novel, as well as the two Finnish translations. The translation strategies used by each translator are analysed. The categories of the translation strategies are ‘translated’, ‘softening’ and ‘omission’. The aim of the thesis is to find out how swearwords are translated from English into Finnish and how retranslations possibly differ from first translations in their way of translating swearwords. The research is conducted as a case in point study from both a quantitative and a qualitative perspective. The quantitative method addresses the presence of swearwords and the frequency of translation strategies used. The qualitative method addresses the choices of translation strategies and their effects on the translation. The results of the thesis provide an insight into a specific example of retranslation and how swearwords are translated from English into Finnish. The study finds that there are multiple possibilities for each translator when choosing an appropriate translation strategy, and multiple reasons behind each translatory choice. This study can be used as motivation for studying the field of retranslation and translating swearwords further. Beyond the scope of this study, there is a multitude of topics and translatory choices that can be researched. It would be beneficial to conduct further study into the translation of swearwords in general, as well as with The Catcher in the Rye and the Finnish translations Sieppari ruispellossa as the cases in point.
Keywords: retranslation, swearword, The Catcher in the Rye, translation strategy